Women empowerment, attitude toward risk-taking and entrepreneurial intention in the hospitality industry - Chanin Yoopetch (2020)
© 2020, Emerald Publishing Limited. Purpose: First, this study aims to investigate the factors affecting entrepreneurial intentions. Second, it is to identify the influential factors with the highest influence on entrepreneurial intention. Design/methodology/approach: The sample of the current study was female employees in various hospitality firms, including restaurants, hotels and wellness services. The questionnaire was developed based on past research studies and was tested for reliability prior to the full set of data collection. To represent the early to mid-level career women in hospitality, female employees with at least one-year experience from hospitality businesses, such as restaurants and hotels, participated in the study and total usable samples were 416. Findings: The findings demonstrated that attitude toward risk-taking, self-efficacy, subjective norm and empowerment is significantly influential to the entrepreneurial intention of the women in the hospitality industry. Based on the data analysis, attitude toward risk-taking has the highest influence on entrepreneurial intention. In other words, with a positive attitude toward risk-taking, female employees showed the greatest tendency to start their own business. Research limitations/implications: The current study extended the theory of planned behavior in that it can be used to explain the women’s entrepreneurial intention with subjective norms, attitudes and self-efficacy. The study also highlighted the flexibility of the theory in allowing the researchers to add external variables to help further investigate the relationships among all the factors in the models. Practical implications: To highlight the opportunity to promote more equality and diversity in the business management environments, the results from the study promoted the roles of women entrepreneurs to support hospitality business development. One of the most influential factors is the attitude toward risk-taking. This suggested that with the positive attitude toward risk, the respondents have higher entrepreneurial intentions. Promoting and sharing the success stories of female entrepreneurs can affect the attitude of female employees and raise their interests toward becoming entrepreneurs. Originality/value: The current study provided a unique investigation on the early to mid-level career hospitality female employees to explore their intention to be entrepreneurs. This research offered the extension of the theory of planned behavior in the context of entrepreneurship.